Semantic Preview Benefit in Eye Movements During Reading: A Parafoveal Fast-Priming Study. - Hohenstein, Sven; Laubrock, Jochen; Kliegl, Reinhold (Journal of Experimental Psychology. Learning, Memory & Cognition, 2010)
Eye movements in reading are sensitive to foveal and parafoveal word features. Whereas the influence of orthographic or phonological parafoveal information on gaze control is undisputed, there has been no reliable evidence for early parafoveal extraction of semantic information in alphabetic script Using a novel combination of the gaze-contingent fast-priming and boundary paradigms, we demonstrate semantic preview benefit when a semantically related parafoveal word was available during the initial 125 ms of a fixation on the pretarget word (Experiments 1 and 2). When the target location was made more salient, significant parafoveal semantic priming occurred only at 80 ms (Experiment 3). Finally, with short primes only (20, 40, 60 ms), effects were not significant but were numerically in the expected direction for 40 and 60 ms (Experiment 4). In all experiments, fixation durations on the target word increased with prime durations under all conditions. The evidence for extraction of semantic information from the parafoveal word favors an explanation in terms of parallel word processing in reading. Reprinted by permission of the publisher.